KOMPOSISI GULMA PADA AREAL PERTANAMAN GANDARIA (Bouea macrophylla) DI NEGERI HATIVE BESAR KECAMATAN TELUK AMBON - Lea Miranti Ratuilwaly; Elia L. Madubun; Rhony E. Ririhena (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
This study aimed to identify the types of weeds and determine the dominant types in the gandaria planting area in Negeri Hative Besar, Teluk Ambon District. This study used a vegetation survey method to collect data through field observations. Based on the analysis, 16 types of weeds from 14 families were found, dominated by broadleaf weeds (SDR 56.91%), fern weeds (SDR 43.06%), perennial weeds (SDR 95.51%) and annual weeds (SDR 4.46%). There were 6 dominant weeds, namely Piper betle L. (SDR 22.73%), Thelypteris unita, SDR 14.38%), Selaginella wildenowi (SDR 13.91%), Nephrolepis biserrata (SDR 11.13%), Philodendron ornatum (SDR 9.71%), and Ficus maxima Mill (SDR 6.73%). Environmental factors such as acidic soil pH (5.7), soil moisture of 51%, air temperature of 28°C, irregular planting distance and old age of gandaria plants, contributed to the dominance of broadleaf weeds and annual weeds. Category D weeds, such as Piper betle L., Thelypteris unita, Selaginella wildenowi, Nephrolepis biserrata, and Philodendron ornatum, as well as the harmful weed Ficus maxima Mill of category B need to be controlled because of their ability to compete with the main crop.